METODE TRIPLE EXPONENTIAL SMOOTHING TIPE BROWN PADA PERAMALAN PRODUKSI PADI PROVINSI JAWA TENGAH - Meta Kurniawati (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2021)
Paddy is one of the staple food crops that almost all Indonesians consume every day. Central Java Province is one of the national food buffer provinces, therefore a model is needed to predict the amount of paddy production in Central Java Province for the future. The amount of paddy production in Central Java Province is not constant and fluctuates every year, so the one-parameter Triple Exponential Smoothing model of the Brown type is used to predict the amount of paddy production in Central Java Province. Based on the results of the analysis of the data, it was obtained that the one-parameter Triple Exponential Smoothing model of the Brown type which is appropriate to be used to predict the amount of paddy production in Central Java Province is F28+m=9485520,31-536660,01(m)+(0,5)(-91215,38)(m2), where the number of periods from 1 to 5.